Ways out of war peacemakers in the Middle East and Balkans (Palgrave Macmillan, 2012)
"How do peacemakers end wars? This book explores the work of ten diplomats who were charged with negotiating conclusions to intractable conflicts in the Middle East and Balkans. The first study to combine the outlooks of practitioners and academics, Ways out of War shows how peacemaking has struggled to respond to new forms of war,especially asymmetrical warfare between state and non- state actors. It shows these diplomats straining to solve major challenges, such as negotiating with war criminals,balancing peace against justice, handling spoilers,setting the timing of peace initiatives, and building or rebuilding state structures. By focusing on these questions from individual peacemakers' points of view,Ways out of War paints a vivid picture of peacemaking, one with full scope for the play of personalities--but one, too, that is critical, comparative, and fully informed by theoretical literature. It will make compelling and essential reading for all students of negotiation and conflict resolution, as well as for any reader who takes an interest in the Balkans, the Middle East, or the ten notable diplomats at its heart"--cProvided by publisher